The phosphorylation and nuclear localization of the co-chaperone murine stress-inducible protein 1 - Longshaw, Victoria Mary (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2003)
The co-chaperone murine stress-inducible protein 1 (mSTI1), a heat shock protein 70 (Hsp70)/ heat shock protein 90 (Hsp90) organizing protein (Hop) homologue, mediates the assembly of the Hsp70/Hsp90 chaperone heterocomplex. mSTI1 is phosphorylated in vitro by cell cycle kinases, proximal to a putative nuclear localization signal (NLS), substantiating a predicted CKII-cdc2-NLS (CcN) motif at position 189-239. Stable transfectants of NIH 3T3 fibroblasts that expressed mSTI1-EGFP, NLSmSTI1-EGFP and EGFP, were prepared. Fluorescence microscopy revealed mSTI1 was cytoplasmically localized, and that this localization was not affected by the fusion of mSTI1 with the EGFP moiety. NLSmSTI1-EGFP was targeted to the nucleus compared to EGFP, suggesting that the NLSmSTI1 was a functional NLS. The localization of mSTI1 was determined under normal and heat shock conditions, inhibition of nuclear export (leptomycin B), inhibition of CKII 5,6-dichlorobenzimidazole riboside, DRB), inhibition of cdc2 kinase (olomoucine), and G1/S phase arrest (hydroxyurea). mSTI1-EGFP and mSTI1 were excluded from the nucleus in the majority of resting cells, but accumulated in the nucleus following leptomycin B treatment, implying that mSTI1 possibly undergoes a functional import process, and export via the chromosomal region maintenance 1 (CRM-1)-mediated export pathway. Hydroxyurea and olomoucine (but not DRB or heat shock) treatment increased the proportion of cells in which mSTI1-EGFP exhibited cytoplasmic and nuclear localization. 2D gel electrophoresis detected three endogenous mSTI1 isoforms, which changed following hydroxyurea treatment. Furthermore, point inactivation and mimicking of phosphorylatable residues in mSTI1 altered the translocation of the protein and the isoform composition. Modification of mSTI1 at S189 and T198 decreased the number of isoforms of mSTI1-EGFP, suggesting that the protein is modified at these sites in vivo. The removal of the in vitro cdc2 kinase site at T198 promoted a nuclear localization during G1/S phase arrest. Therefore active cdc2 kinase, but not CKII, may be required for cytoplasmic localization of mSTI1. The CKII site appears to have no regulatory role under heat shock conditions or during the cell cycle. In vitro phosphorylation studies on untagged mSTI1 further supported the prediction that S189 is the only site recognised by CKII. The cdc2 kinase site at T198, however, although the major site, was not the only site phosphorylated in vitro. However, mSTI1 and cdc2 kinase did not interact in a detectable stable complex. Bioinformatic analysis of mSTI1 revealed NLS residues were conserved in STI1 proteins, and the NLS and TPR2A motifs were in close proximity. This may have mechanistic implications for the formation of the Hsp90-mSTI1 heterocomplex. The cytoplasmic or nuclear localization of mSTI1 is predicted to be the result of a dynamic equilibrium between nuclear import and nuclear export, the fulcrum of which may be shifted under different cell cycle conditions. These data provide the first evidence of regulated nuclear import/export of a major Hsp70/Hsp90 co-chaperone, and the regulation of this nuclear import by cell cycle status and cell cycle kinases.
Keywords: Phosphorylation; Proteins; Heat shock proteins